The end of the idyll? Post-crisis conservation and amenity migration in natural protected areas. (April 2017) - Cortes-Vazquez, Jose A.
Abstract: The 2008 economic crisis and the introduction of austerity policies and values after the crisis are transforming the management of natural protected areas in the global North. Communities of amenity migrants living in these areas have been impacted by such issues as budgetary cuts and state disinvestments in conservation. Important threats to their expectations of an alternative life in a natural idyll are changing the attitudes of amenity migrants towards conservation and rural regions. In this paper, I analyse the main changes in their livelihood and lifestyles in two different natural parks in Spain. The main goal of this analysis is to stimulate a debate about the social impacts of new conservation strategies in the post-crisis context, with particular attention to multi-functional, post-productive rural spaces such as amenity destinations. Highlights: Conservation policies in the global North are changing in the post-crisis, austerity context. The management of natural protected areas has been affected by budgetary cuts and state disinvestments. Social impacts of austerity conservation include livelihood and lifestyle changes among amenity migrants. Amenity migrants are developing feelings of disillusionment with rural areas and critical attitudes towards conservation. These changes reveal the reconfiguration of power relations within post-productive regions after the crisis.